BASIS DATA UNTUK MENGEMBANGKAN SISTEM INFORMASI SEKOLAH - Hamid, Ahmad Abu (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2018)
The purpose of this policy study was for identifying database that could be used to develop a school information system (SIS) and for identifying external and internal stake holders that could be used as data and information to be filed in SIS. The results of the study could be used to make recommendation for schools about the merits of building an SIS, intranet, and internet system. As a case study, this research was held in State Senior High School 1, Jetis, Bantul. Data were gathered from interviews and documentation. Evaluative analysis was used to yield research results and descriptive analysis was used to formulate the recommendation to be extended to the schools. Data analyses and discussion brought about these conclusions and recommendation:(1) Structure database were available that could be used to develop an SIS, (2) Those database could be categorized into specific data and information about the institution, curriculum, school's infrastructure, teachers, instruction, grades, students, new student admission process, alumnus, school's library, worker, and school's monetary, (3) Teachers, students, functionaries of State Senior High School 1, Jetis and the public could access data and information kept in the SIS, and (4) The schools may be expected to build an SIS, intranet, and internet.